Studi Histopatologi Limpa dan Bursa Fabricious Ayam Berpenyakit Tetelo (Newcastle Disease) pada Kasus Lapang (HISTOPATHOLOGY STUDIES ON SPLEEN AND BURSA OF FABRICIUS OF NEWCASTLE DISEASE CHICKHENS FROM FIELD CASE) - Etriwati, Etriwati; Handharyani, Ekowati; Setiyaningsih, Surachmi (Jurnal Veteriner; Vol 18 No 4 (2017)DO - 10.19087/jveteriner.2017.18.4.510, 2018)
Newcastle Disease is a highly contagious and very virulent avian disease in all of poultry. The aims of this study were to determine the lesions and distribution of Newcastle disease virus on spleen and bursa of Fabricous of Newcastle disease chickhens from field cases. The sample used in this study were the spleen and bursa Fabricious organ of ten cases of suspect Newcastle disease. Haematoxylin and eosin staining examination was performed determine of cell morphology and distribution of the virus by immunohistochemical staining. The distribution of the lesions and the degree of reaction were determined by the category immunopositive mild, moderate and severe. Gross lesion on spleen, including swollen, fragile and necrotic multifocal. Histopathological lesions showed hyperemia/congestion and depletion of lymphoid cells. Immunopositive reaction found in lymphoid cells of red pulp and lymphoid cells in lymphoid follicles. Bursa of Fabricious showed atrophy and hyperemia/congestion with histopatological lesions hemorrhages, lymphoid cells in lymphoid follicles undergo necrosis and depletion of lymphoid follicles. Immunopositif reaction was observed in lymphoid cells in the mantle zone of lymphoid follicles. Newcastle disease from field cases cause damage to the spleen and bursa of Fabricius with degrees lesions and virus distribution in the organs are severe.
Keywords: imunohistokimia, Newcastle disease, limpa, bursa Fabricious